Strategi Kepala Sekolah Dalam Pengembangan Kompetensi Profesional Guru - Anis Zohriah; Rijal Firdaos; Zaimul Ubad (Peneliti.net, 2023)
This study examines and examines the Principal's Strategy in Developing Teacher Professional Competence at Al Irsyad Waringinkurung Middle School and Raudhatul Jannah Junior High School Cilegon. The purpose of this study was to determine the professional competence of teachers at SMP Al Irsyad Waringinkurung and SMPIT Raudhatul Jannah Cilegon, to find out the obstacles faced in developing professional competence of teachers at SMP Al Irsyad Waringinkurung and SMPIT Raudhatul Jannah Cilegon, and to know the principal's strategy in developing Professional Competence of Teachers at SMP Al Irsyad Waringinkurung and SMPIT Raudhatul Jannah Cilegon. In this study, the research method used is qualitative with descriptive qualitative research, research that seeks to describe and interpret existing data, besides that it is limited to efforts to reveal a problem or situation as it is (1) Professional Competence of Teachers at SMP Al Irsyad Waringinkurung and SMPIT Raudhatul Jannah Cilegon, (2) Obstacles to Principals in Developing Professional Competence of Teachers at SMP Al Irsyad Waringinkurung and SMPIT Raudhatul Jannah Cilegon , (3) Principal's Strategy in Developing Teacher Professional Competence at Al Irsyad Waringinkurung Middle School and Raudhatul Jannah Junior High School Cilegon. The obstacles faced are related to facilities and infrastructure, limited budget, and from the human resources of the teachers themselves. The Principal's Strategy in Developing Teacher Professional Competence is through discussions, meetings, professional and emotional approaches to provide a forum and involve teachers in activities in the context of developing teacher professional competencies